Optimization of Analysis Method on Total Phenol Content and Antioxidant Activity in Peel and Seeds of White Pomegranate (Punica Granatum L.) - Faisal; Ramadhan, Majida; Rafsanjani, Ramizard; Januarista, Terra (Universitas Brawijaya, 2025)
Pomegranate (Punica granatum L.) peel and seeds are rich in bioactive compounds, particularly phenolics, which contribute significantly to their antioxidant properties. This study aimed to determine the total phenolic content (TPC) and antioxidant activity of white pomegranate peel and seed extracts. TPC was measured using theFolin–Ciocalteu method, while antioxidant activity was assessed via the DPPH radical scavenging assay. Maceration extraction was employed using a 1:1 ethanol–distilled water solvent system. The TPC values of the peel and seed extracts were 99.909 µg/g and 3.424 µg/g samples, respectively, indicating a substantially higher phenolic concentration in the peel. Antioxidant activity, expressed as IC50, was 17.361 ppm for the peel and 26.378 ppm for the seeds, categorizing both as possessing very strong antioxidant potential. The correlation between phenolic content and antioxidant capacity reinforces the role of phenolics as key contributors to antioxidant activity. These results underscore the importance of selecting optimal extraction methods to enhance bioactive compound recovery. The strong antioxidant activity of both peel and seed extracts highlights their potential application as natural antioxidants in the food and pharmaceutical industries.